English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-10-30 09:59:41 · 4 answers · asked by christiangirl_63 1 in Science & Mathematics Mathematics

4 answers

okay

(sinx)(sinx/cosx)

(sinx)(sinx)(1/cosx)
(sinx^2)(secx)

this makes no sense because you have to have it set equal to something...like cosx^2+sinx^2=1 or something

2006-10-30 10:04:42 · answer #1 · answered by Anonymous · 2 0

= (sin x)*(sin x / cos x)
= sin^2 (x) / cos x
= [(1 - cos2x)sec x] / 2

Note that 1/cos x = sec x

And cos2x is derived from here:
cos2x = 1 - 2sin^2 (x)
2sin^2(x) = 1 - cos 2x
sin^2(x) = (1 - cos 2x)/2

There are many ways to solve it actually, it's up to your own creativity to obtain a solution for it.

2006-10-30 18:22:52 · answer #2 · answered by forty*winks 1 · 0 0

tanx = sin x/cos x
(sin x)(tan x) = (sin x)(sinx/cosx) = (sinx)^2 / cosx
(sinx)^2 + (cosx)^2 = 1 so (sinx)^2 = 1 - (cosx)^2
(sinx)(tanx) = (1 -(cosx)^2)/cosx

2006-10-30 18:18:37 · answer #3 · answered by MsMath 7 · 0 0

(sinx)(tanx) = (sinx)(sinx/cosx) = (sinx^2)/(cosx) = (1 - cos(x)^2)/(cos(x)) = (1/(cos(x))) - cos(x) = sec(x) - cos(x)

only if your problem was (sin(x))(cot(x)) = (sin(x))(cos(x)/sin(x)) = cos(x)

2006-10-30 19:16:07 · answer #4 · answered by Sherman81 6 · 0 0

fedest.com, questions and answers